Relationship of Knowledge, Attitudes and Social Status of Family Heads Against Dengue Prevention Measures in the Oesapa Health Center Work Area in 2020 - Malfret Njaka Mbani; Ribka Limbu; Soleman Landi (Journal of Health and Behavioral Science, 2021)
DHF is an infectious disease caused by the dengue virus and transmitted through the bite of the Aedes aegypti mosquito. The factors that cause a person to suffer from dengue are environmental factors, knowledge, attitudes, and social status. This study aims to analyze the relationship between knowledge, attitudes, and social status of the head of the family on the prevention of DHF. The type of research used is quantitative research with a cross-sectional approach. The number of samples in this study was 100 respondents. The independent variables in this study were knowledge, attitudes, education, work, and income, while the dependent variable was the prevention of dengue fever. The type of data analysis used is chi-square. The results showed that the five variables studied had a relationship with dengue prevention measures. The five variables referred to are knowledge (p = 0.002), attitude (p = 0.006), education (p = 0.003), income (p = 0.007), and work (p = 0.006). Keywords: knowledge, attitude, social status, action, head of the family